The Relationship Between the Performance and the Perceived Stress of Employees - Yeşim Avunduk (Research in Social Sciences and Technology- OpenED Network, 2021)
The study aimed to determine the relationship between the job performance of individuals working in the sports industry and their perceived stress. The sample of the study consisted of a total of 474 people including 361 male and 113 female that working in a private company operating in the sports industry in Istanbul, and they were selected by purposeful sampling method. After the data showed normal distribution; Independent t-test, ANOVA and Pearson Correlation analysis were used to analyse the data. According to the result of the analysis, there was no statistically significant difference found between the job performance and perceived stress levels of the participants according to their marital status and educational status. A significant difference was found in the perceived stress levels and job performances of the individuals according to their gender and working period in the workplace. Finally, it was found that there was a negative and low-level relationship between the perceived stress scale and job performance scale. As a result, it was determined that the stress perceived by the individuals and their job performance levels differed according to the socio-demographic characteristics of the individuals, and the higher the stress levels perceived by the individuals, the lower their job performance were.